2010
DOI: 10.1227/01.neu.0000373013.75994.cd
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Stem Cells

Abstract: Research into the capacity of "pituitary stem cells" to differentiate in vitro and in vivo will clarify the mechanisms for regulation of these cells. As pituitary stem cells are better understood, clinical applications like the treatment of pituitary adenomas and the implantation of pituitary stem cells for hormonal deficiencies may be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…These findings support a potential role for adult pituitary stem cells in pituitary adenomas. Almeida et al suggested that the occurrence of plurihormonal and null cell-type adenomas (no distinguishable ultrastructural, immunohistochemical, or histologic characteristics of recognized adenohypophyseal cell types) supports the hypothesis that pituitary stem cells may be a potential source of pituitary adenomas ( De Ameida et al, 2010 ). Radian et al found that GH-and thyroid-stimulating hormone (TSH)-secreting cells share common progenitor cell expression.…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support a potential role for adult pituitary stem cells in pituitary adenomas. Almeida et al suggested that the occurrence of plurihormonal and null cell-type adenomas (no distinguishable ultrastructural, immunohistochemical, or histologic characteristics of recognized adenohypophyseal cell types) supports the hypothesis that pituitary stem cells may be a potential source of pituitary adenomas ( De Ameida et al, 2010 ). Radian et al found that GH-and thyroid-stimulating hormone (TSH)-secreting cells share common progenitor cell expression.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…De Ameida et al, 2010).Radian et al found that GH-and thyroid-stimulating hormone (TSH)secreting cells share common progenitor cell expression. This suggests that TSH adenomas originate from pituitary stem cells that differentiate into GH, PRL, or TSH cells, which may play a role in the pathogenesis of TSH-secreting PPA…”
mentioning
confidence: 99%
“…In addition, the histochemical analyses also indicate keratinization in CPs’ epithelial cells ( 25 - 27 ). The second theory postulates that CPs arise from pituitary progenitor or stem cells representing embryonal remnants of Rathke's pouch epithelium ( 28 - 33 ). Studies in mouse models have provided insights into the importance of stem cells in the tumorigenesis of craniopharyngiomas ( 34 ).…”
Section: Introductionmentioning
confidence: 99%